2020
DOI: 10.1007/s00170-020-06318-2
|View full text |Cite
|
Sign up to set email alerts
|

Fused filament fabrication of commercial conductive filaments: experimental study on the process parameters aimed at the minimization, repeatability and thermal characterization of electrical resistance

Abstract: Nowadays, a challenging scenario involving additive manufacturing (AM), or 3D printing, relates to concerns on the manufacturing of electronic devices. In particular, the possibility of using fused filament fabrication (FFF) technology, which is well known for being very widespread and inexpensive, to fabricate structures with embedded sensing elements, is really appealing. Several researchers in this field have highlighted the high electrical resistance values and variability in 3D-printed strain sensors made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Ultrasonic dispersion [34], surface treatment by surfactants [35], chemical modifications [36], and grafting improve the CNTs-polymer matrices compatibility [26]. Lately, filled polymers with electrically conductive nanowires or particles have been 3D printed to produce electronic devices on several substrates [37]. In addition, utilizing the 3D printing approach to design pressure sensors is another application in recent articles [38].…”
Section: D Printing Of Modified Cnt Nanocompositesmentioning
confidence: 99%
“…Ultrasonic dispersion [34], surface treatment by surfactants [35], chemical modifications [36], and grafting improve the CNTs-polymer matrices compatibility [26]. Lately, filled polymers with electrically conductive nanowires or particles have been 3D printed to produce electronic devices on several substrates [37]. In addition, utilizing the 3D printing approach to design pressure sensors is another application in recent articles [38].…”
Section: D Printing Of Modified Cnt Nanocompositesmentioning
confidence: 99%
“…Several studies have been performed to reduce the gap of knowledge in the field of MeX-manufactured sensors: Arh et al [5] proposed an experimental method to identify the dynamic piezo resistivity of unidirectionally printed structures providing coefficients needful for the building of analytical and numerical models; Cardenas et al [6,7] used high-intensity pulsed light to increase of two orders of magnitude the conductance of the tracks made up of commercial conductive filaments; Stano et al [8], exploiting the Design of Experiment (DoE) approach, found out a relationship between process parameters (layer height and printing orientation) and electrical resistance (and variability) minimization; Maurel et al [9] defined a novel framework to direct 3D print ion-lithium battery.…”
Section: Introductionmentioning
confidence: 99%
“…The anisotropy in the electrical properties can be explained by means of interfacial and inter-layer contact resistance, which is believed to originate from imperfect bonding conditions (e.g. the presence of voids) [ 35 , 36 , 37 , 38 ] and the inhomogeneous distribution of the conductive particles (especially in between traxels and layers) [ 27 , 39 , 40 , 41 ]. For low numbers of layers, the thickness variation is also of importance, as Gnanasekaran et al showed for a varying layer thickness with a factor of due to ridges [ 27 ].…”
Section: Introductionmentioning
confidence: 99%